Performance evaluation of supported ionic liquid membrane for removal of phenol - Nosrati, S.; Jayakumar, N.S.; Hashim, M.A. (Elsevier, 2011)
This work evaluates the performance of ionic liquid in supported liquid membrane (SLM) for the removal of phenol from wastewater. Ionic liquids are organic salts entirely composed of organic cations and either organic or inorganic anions. Due to the fact that the vapor pressure of ionic liquid is not detectable and they are sparingly soluble in most conventional solvents, they can be applied in SLM as the organic phase. In this work, 1-n-alkyl-3-methylimidazolium salts, [C(n)MIM](+)[X](-) have been investigated so as to determine an optimal supported ionic liquid membrane. The effect of operational parameters such as pH, stirring speed and the concentration of stripping agent has been studied, and an evaluation of different membrane supports were also carried out. With a minimal amount of the ionic liquid 1-Butyl-3-methylimidazolium hydrogensulfate, 85% phenol removal could be achieved by using polytetrafluoroethylene hydrophobic membrane filter in the SLM.